LEARNING HEALTH IN AND FOR SCHOOL MEDIATED BY DIGITAL INFORMATION AND COMMUNICATION TECHNOLOGIES: RESULT OF STUDIES IN BRAZIL - Costa Filho, Roraima Alves da; Iaochite, Roberto Tadeu [UNESP] (Univ Estadual Campinas, Fac Educacao, 2021)
Teachers believe that the health education should be addressed by peers with initial training linked to the area. In-service training mediated by information communications technology (ICT) can be a strategy to disseminate knowledge related to health promotion and change conceptions and beliefs about who is responsible for developing it at school. Although there are some studies on the subject, it is necessary to know how they are getting results and what factors can be associated to the success of a course mediated by ICT. Thus, this review aimed to critically analyze research results obtained through in-service training for teachers mediated by ICT and factors that were associated with teacher learning. This state-of-the-art review analyzed 11 studies on continuing teacher education mediated by ICT on the topic of health education. As result, learning was found to be related to three factors: personal (knowledge associated to content and technology), behavioral (interaction, engagement and learning strategies), and environmental (structure and format of the course and tutoring processes). It is understood that training mediated by ICT can be important for the development of teachers, the training processes, and the quality of teaching in Basic Education. However, more attention needs to be addressed to how these processes occur.
Keywords: In-service teacher training; Literature review; Distance education